Ternary polynomial based key management scheme for wireless sensor network - Zhi-tao GUAN; Yue XU; Jun WU (Tongxin xuebao)
A ternary polynomial based key management (KMTP) scheme was proposed,which is effective in cluster based wireless sensor networks.Firstly,the base station will give each node one unique identi ier to ensure the validity of the node.Then,algorithm of the inner-cluster and inter-cluster key pre-distribution based on the ternary polynomial of the same order was stated,which can ensure the value of the cracking threshold is bigger than the number of nodes of a clus-ter and all clusters separately,which means it's very hard to be cracked even all nodes of a cluster or all clusters are com-promised.To assure the communication security,inter-cluster multi-hop routing mechanism was designed based on con-structing secure conjunct neighbor table.Finally,the updating parameter and the updating authentication number were in-troduced in rekeying phase.The analysis shows that the proposed scheme can meet the security requirement of key man-agement,and it also has less computation cost and storage cost than the existing schemes.